The prevalence of simian malaria in wild long-tailed macaques throughout Peninsular Malaysia - Shahhaziq Shahari; Mohd Lutfi Bin Abdullah; Anis Adlina Binti Isman Rohimly; Norsharina Binti Ashrat; Amirah Amir; Wahib Mohammed Mohsen Atroosh; Mun Yik Fong; Yee Ling Lau (Scientific Reports, 2024)
Abstract The parasite Plasmodium knowlesi has been the sole cause of malaria in Malaysia from 2018 to 2022. The persistence of this zoonotic species has hampered Malaysia’s progress towards achieving the malaria-free status awarded by the World Health Organisation (WHO). Due to the zoonotic nature of P. knowlesi infections, it is important to study the prevalence of the parasite in the macaque host, the long-tailed macaque (Macaca fascicularis). Apart from P. knowlesi, the long-tailed macaque is also able to harbour Plasmodium cynomolgi, Plasmodium inui, Plasmodium caotneyi and Plasmodium fieldi. Here we report the prevalence of the 5 simian malaria parasites in the wild long-tailed macaque population in 12 out of the 13 states in Peninsular Malaysia using a nested PCR approach targeting the 18s ribosomal RNA (18s rRNA) gene. It was found that all five Plasmodium species were widely distributed throughout Peninsular Malaysia except for states with major cities such as Kuala Lumpur and Putrajaya. Of note, Pahang reported a malaria prevalence of 100% in the long-tailed macaque population, identifying it as a potential hotspot for zoonotic transmission. Overall, this study shows the distribution of the 5 simian malaria parasite species throughout Peninsular Malaysia, the data of which could be used to guide future malaria control interventions to target zoonotic malaria.